Dose Characterization of the Investigational Anticancer Drug Tigilanol Tiglate (EBC-46) in the Local Treatment of Canine Mast Cell Tumors - Miller, Jane; Campbell, Justine; Blum, Andrew; Reddell, Paul; Gordon, Victoria; Schmidt, Peter; Lowden, Stewart (Frontiers in Veterinary Science, 2019)
Mast cell tumor (MCT) is the most common cutaneous neoplasm in dogs and wide surgical resection is the current first-line treatment. However, recurrence is common and often requires more specialist and expensive therapies. Tigilanol tiglate is a novel small molecule drug delivered by intratumoral injection that is currently under development to provide a new option for treating MCT. The aim of this study was to characterize a safe and effective dose of tigilanol tiglate for canine MCT and to gather preliminary data on the drug’s pharmacokinetics. A multicenter, open-label, uncontrolled, non-randomized, dose de-escalation design was used. Eligibility was MCT stage I/IIa and a tumor size of 0.1-6.0 cm3. Dosing was based on tumor size (50% v/v tumor) and 3 drug concentrations (1.0, 0.5, 0.2 mg/mL) were evaluated. Twenty-seven dogs were treated in 3 dose de-escalation cohorts (10, 10, 7). Efficacy at 21 days was defined using international accepted solid tumor response criteria (RECIST). Greatest efficacy (90% complete response) was observed at the highest drug concentration (1.0 mg/mL) and adverse events were generally low grade, mild and transient, and directly associated with the mode of action of the drug. Hematological and serum biochemistry were generally unremarkable with plasma concentration curves typical of a non-intravenous parenteral medication. Intratumoral treatment of MCT with tigilanol tiglate at a concentration of 1.0 mg/mL was highly efficacious and well tolerated. These results support the drug’s further development for the treatment of MCT and other solid tumors.